1999
DOI: 10.1007/bf02461181
|View full text |Cite
|
Sign up to set email alerts
|

Educating science teachers for the sociocultural diversity of urban schools

Abstract: This interpretive study of the preparation of science teachers for urban high schools explored the extent to which learning to teach was facilitated by the methods courses, cooperating teachers and university supervisors. Because the methods course was minimally effective in addressing the needs of teaching low track students from conditions of poverty the methods instructor, Tobin, decided to be a teacher-researcher with such students. He joined Smith, a student teacher and Seiler, a doctoral student, in an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…I ascribe the label “invisibility” to this literature because in this work the science education of African Americans is obfuscated by use of demographic labels that equate “African American”‐ness with alternative (and sometimes inaccurate) demographic characteristics, such as “urban”‐ness or “minority”‐ness. Among this literature is work that misrepresents African American populations as “urban,” “inner city,” “minority,” “at‐risk,” “underrepresented,” or “underprivileged” (e.g., Atwater, Wiggins, & Gardner, 1995; Brickhouse & Potter, 2001; Carmichael & Sevenair, 1991; Elmesky, 2011; Emdin, 2009; Thomas, 1986; Tobin, Seiler, & Smith, 1999). So we often find researchers speaking of “urban” schools or “minority” students when the schools and students under investigation are largely African American.…”
Section: African Americans In Science Education Literaturementioning
confidence: 99%
“…I ascribe the label “invisibility” to this literature because in this work the science education of African Americans is obfuscated by use of demographic labels that equate “African American”‐ness with alternative (and sometimes inaccurate) demographic characteristics, such as “urban”‐ness or “minority”‐ness. Among this literature is work that misrepresents African American populations as “urban,” “inner city,” “minority,” “at‐risk,” “underrepresented,” or “underprivileged” (e.g., Atwater, Wiggins, & Gardner, 1995; Brickhouse & Potter, 2001; Carmichael & Sevenair, 1991; Elmesky, 2011; Emdin, 2009; Thomas, 1986; Tobin, Seiler, & Smith, 1999). So we often find researchers speaking of “urban” schools or “minority” students when the schools and students under investigation are largely African American.…”
Section: African Americans In Science Education Literaturementioning
confidence: 99%
“…Some recent work in science education seems to suggest that one of the most important questions has yet to be asked: Is the referent for the science to be taught appropriate for engaging all as the title of the AAAS (1989) report Science for all Americans: Project 2061 appears to achieve? Thus, it has been suggested that "science for all" has to be reframed (at least in some context) so that it is appropriate for students in poverty and destitute homing projects (Barton, 1998;Tobin, Seiler, & Smith, 1999). Another suggestion is to deinstitutionalise science education and to make it part of the local community where students contribute their part to the overall environmental activities (Roth & McGinn, 1997).…”
Section: On Apprenticeship and Power Relationsmentioning
confidence: 95%
“…Tobin et al 1999;Wallace and Louden 2000). Despite multiplicity in perspectives and disciplines, a common vision of effective professional development exists (Loucks-Horsley et al 1990.…”
Section: Principle 1: Consistency With Evidence From Literature On Tementioning
confidence: 95%